Kano Method: Development of Multi-Function Walker Product Attributes - Marodiyah, Inggit; Putra, Boy Isma; Akbar, Ali; Jakaria, Ribangun Bamban (2477 - 6165, 2024)
Sensory and motor disorders experienced by a person can reduce the ability to walk. The triggers for these disorders vary, including age factors. Older adults who are at high risk have limitations in their daily activities. Therefore, they must improve their walking ability using rehabilitation aids (walkers). This study aims to design a multi-function walker that can work optimally in older people. The urgency of this study is that the types of walkers on the market are still limited, so they need to be developed into a multifunctional design. The method used in this study is the Kano method. The expected research results are the development of a design for one type of walker with multiple functions, namely functioning as a walking aid (walker) and functioning as a wheelchair, with a comfortable level of seating and can adjust its height.